Shock Index in Hyperglycemic Patients in the Emergency Medical and Surgical Ward of Dr. Soedono Madiun General Hospital - Azizah, Maura Olifiani; Rachmawati, Dewi; Mulyadi, Arif (Universitas Tribhuwana Tunggadewi, 2024)
Uncontrolled hyperglycemia causes hyperosmolarity, stimulating osmotic diuresis and leading to excessive dehydration which can result in death. Therefore, early detection of hypovolemic shock is necessary for immediate management. The aim of the study is to assess the shock index values in hyperglycemic patients in medical and surgical emergency rooms. Using a descriptive method, this study included a population of hyperglycemic patients from January 30 to March 11, 2023, with a sample of 40 patients meeting the inclusion criteria of diabetic ketoacidosis (DKA) and Hyperosmolar Hyperglycemic State (HHS) complications. The instrument used were observation sheets and shock index assessment indicators. The results showed that 16.7% of respondents with DKA experienced moderate shock, 72.2% mild shock, and 11.1% without shock. Meanwhile, 50% of respondents with HHS experienced severe shock, and 50% moderate shock. Mild shock was most common in DKA due to sufficient body fluids preventing a drop in blood pressure and pulse rate. Conversely, HHS patient exhibited severe and moderate shock because high blood glucose levels caused osmotic diuresis, leading to excessive dehydration. It can be concluded that higher blood glucose levels result in more severe dehydration thus worsening the shock condition